Vertebrate Diversity as a Bioindicator and Conservation Basis to Support Ecotourism in the Sekaroh Forest Area, East Lombok - Yamin, M.; Khairuddin, Khairuddin; Artayasa, I Putu (Jurnal Biologi Tropis, 2024)
Research on vertebrate fauna diversity as a bioindicator and conservation basis to support ecotourism in the Sekaroh Forest Area, East Lombok Regency was conducted in November 2022. The goal is to obtain an accurate description of the existence of vertebrate fauna species and the ecological conditions of the Sekaroh forest area. Data collection was carried out by survey method by way of exploration. The data obtained were analyzed qualitatively and quantitatively calculated by the Index: species diversity according to Shannon-Wienner (H'), type abundance (E), dominance (D), type similarity (IS), and distribution patterns. The results were obtained as many as 536 individuals classified into three classes and 30 species. Reptiles have 39 individuals 5 sp., Aves 208 individuals 15 sp., and Mammals 35 individuals 10 sp. Aves is the most diverse species, while Macaca pascicularis has the largest population. The species diversity index (H') and abundance of vertebrates in the region are relatively high, meaning that environmental and wildlife conditions are relatively good, available and maintained by various factors supporting their survival. All vertebrate species found during surveys and observations are common fauna, their distribution area is wide and easy to find in various locations in various regions. The population of M. fascicularis needs to be controlled as an effort to mitigate agricultural pests and support ecotourism. The involvement of local residents in conservation efforts of M. fascicularis in the Sekaroh Forest Area for security and conflict avoidance.